Conformational studies of oligomeric oxetane-based dipeptide isosteres derived from L-rhamnose or D-xylose. - Johnson, S; Jenkinson, S; Pérez-Victoria, I; Edwards, A; Claridge, T; Tranter, G; Fleet, G; Jones, J (2005)
Conformational investigations have been undertaken on oligomers (dimers, tetramers, hexamers) of five closely related oxetane-based dipeptide isosteres. All the oligomers were subjected to a range of studies by NMR, FT-IR and CD spectroscopy. The oligomers derived from methyl 2,4-anhydro-5-azido-3-O-tert-butyldimethylsilyl-5-deoxy-L-rhamnonate 'monomer' all exhibited evidence of ordered conformations in chloroform and 2,2,2-trifluoroethanol (TFE) solution. 5-Acetamido and N-methylamide derivatives of the L-rhamnonate 'monomer', along with a 'dimer' lacking silyl protection at C-3, were synthesized to ascertain the role of intramolecular interactions. This led to the conclusion that, for the L-rhamnonate oligomers, steric interactions govern the conformational preference observed. The equivalent silyl-protected D-lyxonate oligomers gave ordered CD spectra in TFE solution, but NMR and FT-IR spectroscopy in chloroform solution suggested an irregular, non-hydrogen bonded system. The remaining silyl-protected 6-deoxy-L-altronate, 6-deoxy-D-gulonate and D-fuconate oligomers appear to be characterized by their lack of ordered conformation in TFE and chloroform solution.